2019
DOI: 10.1681/asn.2018090941
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin Type 1 Domain–Containing 7A Localizes to the Slit Diaphragm and Stabilizes Membrane Dynamics of Fully Differentiated Podocytes

Abstract: BackgroundAbout 3%–5% of adults with membranous nephropathy have autoantibodies directed against thrombospondin type 1 domain–containing 7A (THSD7A), a podocyte-expressed transmembrane protein. However, the temporal and spatial expression of THSD7A and its biologic function for podocytes are unknown, information that is needed to understand the effects of THSD7A autoantibodies in this disease.MethodsUsing a variety of microscopic techniques, we analyzed THSD7A localization in postnatal, adult, and autoantibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…NELL-1-associated MN appears to be unique kidney disease associated with overexpression of NELL-1. As is the case for PLA2R and THSD7A, 22 anti-NELL-1 antibodies recognize a conformation-dependent epitope (found both in 280-kDa homodimers and 420-kDa homotrimers formed through a helical coiled-coil domain). Further studies are needed to determine NELL-1 ultrastructural localization at the podocyte and the potential role of anti-NELL-1 antibodies in podocyte adhesion and slit diaphragm stabilization.…”
Section: Discussionmentioning
confidence: 88%
“…NELL-1-associated MN appears to be unique kidney disease associated with overexpression of NELL-1. As is the case for PLA2R and THSD7A, 22 anti-NELL-1 antibodies recognize a conformation-dependent epitope (found both in 280-kDa homodimers and 420-kDa homotrimers formed through a helical coiled-coil domain). Further studies are needed to determine NELL-1 ultrastructural localization at the podocyte and the potential role of anti-NELL-1 antibodies in podocyte adhesion and slit diaphragm stabilization.…”
Section: Discussionmentioning
confidence: 88%
“…54 THSD7A localizes to the slit diaphragm of podocyte foot processes and is associated with enhanced stabilization of the slit diaphragm in cultured podocytes, supporting a pathogenic role. 62 The positivity rate of antibody in serum and tissue is highly correlated. 55 Serum IIF has 92% diagnostic sensitivity and 100% specificity.…”
Section: Thsd7a Mnmentioning
confidence: 99%
“…This finding may suggest that the location of auto-antigenic proteins may determine their ability to cause damage to podocytes. Recently, using a variety of microscopes, it was found that THSD7A localizes at the basal aspect of foot processes, closely following the meanders of the slit diaphragm in human and mice, and the anti-THSD7A antibodies bind THSD7A expressed on the slit diaphragm ( 64 ). In human podocytes, THSD7A expression is accentuated at filopodia and thin arborized protrusions, an expression pattern associated with the decreased membrane activity of cytoskeletal regulators.…”
Section: Auto-antigens and Extrarenal Autoimmune-inducing Phenomenamentioning
confidence: 99%
“…In human podocytes, THSD7A expression is accentuated at filopodia and thin arborized protrusions, an expression pattern associated with the decreased membrane activity of cytoskeletal regulators. Phenotypically, THSD7A expression in human podocytes is associated with an increase in cell size and enhanced adhesion to collagen type IV-coated plates ( 64 ). Again, due to the lack of evidence on the precise localization of PLA2R1, it is currently reasonable to believe in renal pathology that PLA2R1 could also express at the basal domain or slit diaphragm of podocytes and can disrupt the function of podocytes, such as their adhesion ability to collagen type IV (GBM) ( 65 ).…”
Section: Auto-antigens and Extrarenal Autoimmune-inducing Phenomenamentioning
confidence: 99%